Total heavy prefabrication: Santo António dos Cavaleiros (SAC) and Quinta do Morgado (QM) - Alberto Reaes Pinto (Cidades, Comunidades e Território)
Prefabrication is one of the two great methods of industrialized construction that became cost-effective after World War II. The development of such industrialized building techniques was prompted by the great shortage of buildings resulting from the massive destruction of cities, the big demographic explosion and the industrial concentration after World War II (Blachère, 1975).Traditional construction, which was diffused and disorganized, short of skilled labour, materials and energy, came out ineffective. Most European countries came to the conclusion that housing provision, in terms of quantity, speed of construction and price, could only be solved with the use of industrialized construction.The use of heavy prefabrication in Portugal began in the mid-1960s, in order to meet the large national deficits (requiring 500,000 new dwellings per year). The first Portuguese building experience with this kind of technology began in 1964, accomplished by the construction company ICESA - Indústria de Construção e Empreendimentos Turísticos. This presentation will explore two significant case studies built by ICESA: Santo António dos Cavaleiros (SAC), a Housing unit of real estate development, with 42 hectares, located in the Lisbon Metropolitan Area, near the Frielas bridge, Loures, about 2.5km away from the main city centre. Around 3000 dwellings were grouped in small-scale buildings (up to 5 floors) and towers (11 floors). They were divided into several categories, according to the organization of the space, floor area, materials and appliances, and typologies of one to four bedrooms per apartment; and, Quinta do Morgado, a Housing unit located in Lisbon, next to the Encarnação neighbourhood, where a total of 1660 dwellings were spread throughout 20 hectares. The planning, design and construction of this housing complex is the result of a bidding process carried out by the Lisbon City Hall (initially for 1140 houses), to tackle the housing problem of the lower classes.